Global and regional brain volumes normalization in weight-recovered adolescents with anorexia nervosa: preliminary findings of a longitudinal voxel-based morphometry study - Bomba M (Dove Medical Press, 2015)
Monica Bomba,1,* Anna Riva,1,* Sabrina Morzenti,2 Marco Grimaldi,3 Francesca Neri,1 Renata Nacinovich1 1Child and Adolescent Mental Health Department, San Gerardo Hospital, University of Milano-Bicocca, Monza, Italy; 2Medical Physics Department, San Gerardo Hospital, Monza, Italy; 3Department of Radiology, Humanitas Research Hospital, Milan, Italy *These authors contributed equally to this work Abstract: The recent literature on anorexia nervosa (AN) suggests that functional and structural abnormalities of cortico-limbic areas might play a role in the evolution of the disease. We explored global and regional brain volumes in a cross-sectional and follow-up study on adolescents affected by AN. Eleven adolescents with AN underwent a voxel-based morphometry study at time of diagnosis and immediately after weight recovery. Data were compared to volumes carried out in eight healthy, age and sex matched controls. Subjects with AN showed increased cerebrospinal fluid volumes and decreased white and gray matter volumes, when compared to controls. Moreover, significant regional gray matter decrease in insular cortex and cerebellum was found at time of diagnosis. No regional white matter decrease was found between samples and controls. Correlations between psychological evaluation and insular volumes were explored. After weight recovery gray matter volumes normalized while reduced global white matter volumes persisted. Keywords: anorexia nervosa, adolescent, gray matter, insula, voxel-based morphometry study